2007
DOI: 10.1161/circulationaha.107.728303
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Is a Key Mediator of Cerebral Aneurysm Formation

Abstract: Background-Subarachnoid hemorrhage caused by the rupture of cerebral aneurysm (CA) remains a life-threatening disease despite recent diagnostic and therapeutic advancements. Recent studies strongly suggest the active participation of macrophage-mediated chronic inflammatory response in the pathogenesis of CA. We examined the role of nuclear factor-B (NF-B) in the pathogenesis of CA formation in this study. Methods and Results-In experimentally induced CAs in rats, NF-B was activated in cerebral arterial walls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
250
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(259 citation statements)
references
References 32 publications
7
250
0
2
Order By: Relevance
“…Rat CAs were induced as previously described 13,14 (Supplementary Figure 1) in which we have repeatedly demonstrated the similarity of this model with human CAs and suitability as a CA model. 11,15,16 Briefly, under the general anesthesia by pentobarbital (50 mg/kg i.p.…”
Section: Materials and Methods Induction Of Experimentally Induced Camentioning
confidence: 96%
“…Rat CAs were induced as previously described 13,14 (Supplementary Figure 1) in which we have repeatedly demonstrated the similarity of this model with human CAs and suitability as a CA model. 11,15,16 Briefly, under the general anesthesia by pentobarbital (50 mg/kg i.p.…”
Section: Materials and Methods Induction Of Experimentally Induced Camentioning
confidence: 96%
“…In the present study, we fed rats on a 3‐aminopropionitrile–containing diet, which regulates extracellular matrix organization, to facilitate IA formation in this rodent model, as reported previously 3, 9, 11, 12. Importantly, anagliptin treatment did not affect lysyl oxidase activity in the blood (Figure S2), meaning that the effect of anagliptin on IA growth may not directly associate with the regent 3‐aminopropionitrile, an inhibitor of the catalytic activity of lysyl oxidase.…”
Section: Resultsmentioning
confidence: 99%
“…Although surgical clipping and coiling have become established therapies for IAs, effective noninvasive medical therapies that reduce the risk of aneurysm growth do not exist. Recent studies have revealed that chronic inflammatory responses underlie IA growth 3, 4. In fact, several anti‐inflammatory agents inhibit aneurysms in rodent models,5, 6 yet no clinical trial has conclusively demonstrated the effectiveness of these reagents in humans.…”
Section: Introductionmentioning
confidence: 99%
“…This is indicated by the expression of vascular growth factor receptors, proliferation markers, signs of apoptosis and activated intracellular pathways related to growth. [11][12][13] The complement system is a major part of innate immunity, which also regulates the adaptive immune system. Growing evidence points to an important role of comple-ment in injury responses, involving the clearance of tissues from accumulating debris together with phagocytes.…”
mentioning
confidence: 99%